DOI: 10.11606/d.10.2014.tde-01102014-161305
|View full text |Cite
|
Sign up to set email alerts
|

Nutrição proteica de poedeiras comerciais

Abstract: Agradeço a minha prima Juliana por ter me mostrado a profissão de zootecnista. Aos meus pais, Jair e Marilena por sempre apoiarem minhas escolhas, por serem pessoas maravilhosas e mostrarem os caminhos certos a seguir.A minha namorada Camila pela enorme ajuda na confecção da minha dissertação, pelo companheirismo, pelo amor e por ser a pessoa maravilhosa que é.A todos os meus companheiros de trabalho da Agroceres Multimix principalmente Rafael, Livya, Fabio e Patricia, por segurarem a barra durante minhas ausê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
7

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
0
4
0
7
Order By: Relevance
“…In contrast, Bendezu et al (2015) observed that the increase in Met + Cys content coincided with a lower egg weight for laying hens in the first production cycle. Although different studies provide contrasting results, the level of methionine in laying diets is related to egg weight (Bunchasak & Silapasorn, 2005;Brumano, 2009;Gambaro, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Bendezu et al (2015) observed that the increase in Met + Cys content coincided with a lower egg weight for laying hens in the first production cycle. Although different studies provide contrasting results, the level of methionine in laying diets is related to egg weight (Bunchasak & Silapasorn, 2005;Brumano, 2009;Gambaro, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Increased egg production was observed by Solarte, Rostagno, Soares, Silva and Velasquez (2005) when laying hens received 0.684% methionine plus cystine (Met + Cys). According to Gambaro (2014), birds fed 0.77% Met + Cys had higher egg weights, compared to birds fed diets with only 0.66% Met + Cys. Barbosa et al (1999) observed the same change in egg weight when Met + Cys were included in the diet of white and brown egg-laying hens.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, la información disponible sobre los requerimientos nutricionales de metionina + cistina digerible en gallinas ponedoras comerciales ligeras y semipesadas es escasa (D'Agostini et al, 2017). Para estos animales, el ajuste en el nivel de proteína y de aminoácidos en la dieta es esencial, debido a la gran demanda de estos nutrientes para la síntesis del huevo, albumen y yema (Gambaro, 2014).…”
Section: Introductionunclassified
“…Segundo Gambaro (2014), aves que receberam dietas contendo 0,77% de met +cys apresentaram maiores pesos de ovos quando comparados as aves que receberam a dieta com apenas 0,66% de met + cys. Em Barbosa et al (1999), o mesmo comportamento para peso de ovos foi observado, a inclusão de met + cys à dieta de poedeiras de ovos brancos e marrons.…”
Section: Aminoácido Sulfuradounclassified
“…A utilização do aminoácido sulfurado met + cys resulta em, aumento do peso dos ovos (GAMBARO, 2014;BENDEZU et al, 2015;KAKHKI et al, 2016; BARBOSA), altera a porcentagem do conteúdo dos ovos gema, albúmen e casca , produção de ovos (SOLARTE et al, 2005) e minimiza os efeitos poluentes causados pela excreção de N .…”
Section: Aminoácido Sulfuradounclassified